PELIBATAN MASYARAKAT DALAM KEGIATAN KEBUN BIBIT RAKYAT (KBR) DI DESA SOLONSA KECAMATAN WITA PONDA KABUPATEN MOROWALI - Kansil, Asmita Devianti; ,, Golar; Harijanto, Herman (Jurnal Warta Rimba, 2016)
Forest condition in the Solonsa village, Wita Ponda district, Morowali regency and surrounding it is quite alarming nowadays. The damage that causes flood, droughts and landslides are the main factors that triggered the criticality and land degradation in some rural areas of Solonsa. The damage can be rehabilitated by involving the community to participate in a forestry program, in this case, the activity to make people’s nurseries (KBR). The program is devoted to the manufacture enrichment plant reforestation in Solonsa village. This research aimed at finding the community involvement in the activities of the people’s nurseries. This results are expected to be a useful written input to the government and non-governmental organization to carry out the nurseries program activities. The experimental method used in this research. This method is used in solving the problem by exploring the causal relationship of two or more variables through accurate experimentation. Software statistical program for social science (SPSS) used for the easiness data management and provisioning. The results show that the correlation between internal factors and community involvement, in relation to the age factor with the (0,266), education (0,056), the number of dependents (0,182), revenue (-0,163) was low toward the people’s nurseries activity. Key Words: Program, Activity, People’s Nurseries Activity